CROSS-INDUSTRY KNOWLEDGE TRANSFER: APPLYING LUXURY RETAIL MANAGEMENT FRAMEWORKS TO MEDICAL AESTHETICS OPERATIONS - Kuzmichova, Marharyta (Public Management and Policy, 2026)
This article describes how management practices developed in the luxury retail sector can be applied to the operational context of medical aesthetics clinics. The study was conducted at the Arviv Medical Aesthetics clinic network (Miami, Florida, USA) between 2024 and 2026. The author, who has nearly six years of experience as a General Retail Manager at LVMH / Starboard Cruise Services retail chain and heads a clinic without a medical background, systematically implemented four management systems: an inventory tracking and control system; a staff performance measurement and accountability framework; an employee training and development program; and a structured patient service quality standard. The numerical indicators were obtained from reports of the medical information system over three years: the pre-intervention year (March 2023 to February 2024), the first post-implementation year (March 2024 to February 2025), and the second post-implementation year (March 2025 to February 2026). Annual revenue increased from $1,656,894 to $2,034,435 – and was sustained at this level in the third year ($2,034,769) despite a deteriorating external environment. Average revenue per patient visit increased from $347.01 to $463.62. Expenses for goods and supplies decreased by 22 percent. Staff turnover decreased. The percentage of patients making repeat appointments rose markedly. The article separately examines which retail practices can be transferred without modification, which require significant adaptation, and which are simply impossible to apply in a medical setting. It also describes the cultural resistance of medical staff and the specific measures that helped overcome it. The study formalizes these practices into the Cross-Industry Clinical Operations Adaptation Model (CICOA) – a four-system framework that classifies each transferred practice by its transferability and integrates a behavioral component for managing staff resistance – and demonstrates its reproducibility through independent replication at four clinics, with results sustained independently of the author's on-site presence. The model applies beyond medical aesthetics to dental clinics, beauty salons, medical centers, and other highly personalized service organizations.